2020
DOI: 10.1111/ajae.12161
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐Smart Innovations and Rural Poverty in Ethiopia: Exploring Impacts and Pathways

Abstract: Climate‐smart innovations have been receiving increasing attention in policy dialogues for their potential to transform agricultural systems and improve the well‐being and resilience of farm households. Using recent panel data from Ethiopia combined with novel historical weather data, we provide microeconomic evidence of the welfare effects of conservation agriculture (CA), a climate‐smart agricultural practice. We use a panel data endogenous switching regression model to deal with selection bias and farmer he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 81 publications
7
42
0
Order By: Relevance
“…Interestingly, the results also show that adopting all the practices (i.e., I 1 Z 1 R 1 A 1 ) signi cantly increased FI by 49% in East Africa, 82% in West Africa, 48% in Southern Africa and in 50% in the pooled sample, as well as SSF by 59% and 50% for East Africa and the pooled sample, respectively. This corroborates with previous studies which found that adoption of complete packages of SAPs improves households welfare in Africa (e.g., Abdallah et al, 2020;Sardar et al, 2020;Tesfaye et al, 2020). I 0 Z 0 R 1 A 1 0.07 (0.03) ** 0.99 (0.15) *** -0.07 (0.03) ** -0.32 (0.17) ** -0.07 (0.03) ** 0.12 (0.06) * -0.61 (0.13) *** -0.91 (0.45) ** I 1 Z 1 R 1 A 0 0.12 (0.05) *** -5.49 (0.87) *** 0.02 (0.03) -0.20 (0.12) * -0.02 (0.13) -0.38 (0.12) As stated earlier, the Multivalued Treatment Effect model (Cattaneo, 2010;Imbens& Wooldridge, 2009) was estimated to verify consistency of the results.…”
Section: Impact Of Saps On Farm Income and Food Securitysupporting
confidence: 93%
“…Interestingly, the results also show that adopting all the practices (i.e., I 1 Z 1 R 1 A 1 ) signi cantly increased FI by 49% in East Africa, 82% in West Africa, 48% in Southern Africa and in 50% in the pooled sample, as well as SSF by 59% and 50% for East Africa and the pooled sample, respectively. This corroborates with previous studies which found that adoption of complete packages of SAPs improves households welfare in Africa (e.g., Abdallah et al, 2020;Sardar et al, 2020;Tesfaye et al, 2020). I 0 Z 0 R 1 A 1 0.07 (0.03) ** 0.99 (0.15) *** -0.07 (0.03) ** -0.32 (0.17) ** -0.07 (0.03) ** 0.12 (0.06) * -0.61 (0.13) *** -0.91 (0.45) ** I 1 Z 1 R 1 A 0 0.12 (0.05) *** -5.49 (0.87) *** 0.02 (0.03) -0.20 (0.12) * -0.02 (0.13) -0.38 (0.12) As stated earlier, the Multivalued Treatment Effect model (Cattaneo, 2010;Imbens& Wooldridge, 2009) was estimated to verify consistency of the results.…”
Section: Impact Of Saps On Farm Income and Food Securitysupporting
confidence: 93%
“…Interestingly, the results also show that adopting all the practices (i.e., I 1 Z 1 R 1 A 1 ) signi cantly increased FI by 49% in East Africa, 82% in West Africa, 48% in Southern Africa and in 50% in the pooled sample, as well as SSF by 59% and 50% for East Africa and the pooled sample, respectively. This corroborates with previous studies which found that adoption of complete packages of SAPs improves households welfare in Africa (e.g., Abdallah et al, 2020;Sardar et al, 2020;Tesfaye et al, 2020). (Cattaneo, 2010;Imbens& Wooldridge, 2009) was estimated to verify consistency of the results.…”
Section: Impact Of Saps On Farm Income and Food Securitysupporting
confidence: 91%
“…Michler, Tjernström, Verkaart, and Mausch (2019) argued that relative to yield targets, farmers focus more on economic return indicators when making decisions. Based on Khonje et al (2018) and Tesfaye et al (2020), this study used a random utility framework to analyse the adoption of multiple additional agricultural technologies, including IPM, BF, and SI, in a total of seven possible combinations:…”
Section: Methodsmentioning
confidence: 99%
“…In the process of agricultural production, farmers often face a series of technical choices that can be adopted individually or jointly (Feder, Just, & Zilberman, 1985;Mutale, Kalinda, & Kuntashula, 2017;Tesfaye, Blalock, & Tirivayi, 2020). Since Feder (1982) first developed a model to deal with interrelations in the adoption of multiple agricultural technologies (MATs), an increasing number of researchers have studied a variety of technology combination schemes (Cafer & Rikoon, 2018;Khanna, 2001;Kimbi et al, 2021;Wu & Babcock, 1998).…”
Section: Introductionmentioning
confidence: 99%